Optimal Design of Truss Structures Using a Neutrosophic Number Optimization Model under an Indeterminate Environment - Wenzhong Jiang; Jun Ye (Neutrosophic Sets and Systems, 2016)
This paper defines basic operations of neutrosophic numbers and neutrosophic number functions for objective functions and constraints in optimization models. Then, we propose a general neutrosophic number optimization model for the optimal design of truss structures.